2023
DOI: 10.1063/5.0155290
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced bond rupture in single-molecule junctions: Effects of multiple electronic states and vibrational modes

Abstract: Current-induced bond rupture is a fundamental process in nanoelectronic architectures, such as molecular junctions, and scanning tunneling microscopy measurements of molecules at surfaces. The understanding of the underlying mechanisms is important for the design of molecular junctions that are stable at higher bias voltages and is a prerequisite for further developments in the field of current-induced chemistry. In this work, we analyze the mechanisms of current-induced bond rupture employing a recently devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…This is because the current can effectively break the time-reversal symmetry. Such a Berry force has significant effects on the current-induced dynamics. , Second, Subotnik et al recently demonstrated that spin–orbital couplings (SOCs), or complex Hamiltonian, can also lead to a nonzero friction tensor (Lorentz-like Berry force) even when there is no electrochemical difference across the molecular conductor (equilibrium). , The Berry force arising from SOCs can be termed the spin Berry force. In all, the antisymmetric part of the friction tensor can contribute to a Lorentz-like Berry force even without a continuum of electronic states, but it does not affect the energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the current can effectively break the time-reversal symmetry. Such a Berry force has significant effects on the current-induced dynamics. , Second, Subotnik et al recently demonstrated that spin–orbital couplings (SOCs), or complex Hamiltonian, can also lead to a nonzero friction tensor (Lorentz-like Berry force) even when there is no electrochemical difference across the molecular conductor (equilibrium). , The Berry force arising from SOCs can be termed the spin Berry force. In all, the antisymmetric part of the friction tensor can contribute to a Lorentz-like Berry force even without a continuum of electronic states, but it does not affect the energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, voltage-induced spin-crossover has been proposed. , Johannsen and co-workers have demonstrated electron-induced spin switching through scanning tunneling microscope (STM) experiments . In general, the spin transition is dependent on the coupling between molecular vibrations and electronic states, , which is mainly determined by metal–ligand interactions and molecule–substrate couplings in surface-supported transition-metal complexes. , It is shown that current flowing through a molecular device can excite specific vibrational modes, thus enabling spin-crossover via electron–phonon coupling at the single-molecule level. However, further research is needed to establish the link between current-induced vibrational excitation and spin transition in single-molecule junctions.…”
mentioning
confidence: 99%